TRANSFORMATIONAL LEADERSHIP: TRADITIONAL PESANTREN TOWARDS SUFISM-BASED ENTREPRENEURIAL PESANTREN - Ervina Zulfa Bani Umar; Suheri; Ahmadi Pramuja; Husein Muhammad Fajrul Islam (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
This study aims first, to explore and interpret the implementation of Kiai Muhammad Holid's transformational leadership. Second, to explore Kiai's leadership strategies in the transformation process from traditional pesantren to Sufism-based entrepreneurial pesantren. Third, to explore the effectiveness of Kiai Muhammad Holid's transformational leadership. The research method used is qualitative with the type of field research conducted at the Salafiyah Abu Zairi Pakisan Tlogosari Bondowoso Islamic Boarding School. Data collection techniques utilize documentation, deep interviews, and passive participation observation. Furthermore, the data validity test uses observation persistence, triangulation of sources and techniques by adopting the Miles, Huberman and Saldana interactive model data analysis which consists of data collection, data condensation, data presentation, conclusion drawing/verification. The results of this study show that first, Kiai Muhammad Holid successfully implemented transformational leadership through the main elements of Bass' (1999) theory which include: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration to all pesantren residents. Second, to realize Sufism-based entrepreneurial pesantren, Kiai Muhammad Holid formed an active entrepreneurial education system in formal instution and tasawuf amaliyah education in pesantren. Third, Kiai Muhammad Holid's transformational leadership provides real effectiveness in increasing the commitment, involvement, and loyalty of educators and students in the boarding school. Keywords: Transformational Leadership, Entrepreneurial Pesantren, Sufism Pesantren.     Abstrak Penelitian ini bertujuan pertama, untuk mengeksplorasi serta menginterpretasikan implementasi kepemimpinan transformasional Kiai Muhammad Holid. Kedua, mengeksplorasi strategi kepemimpinan Kiai dalam proses transformasi dari pesantren tradisional menuju pesantren entrepreneur berbasis sufisme. Ketiga, mengeksplorasi efektivitas kepemimpinan transformasional kiai Muhammad Holid. Metode penelitian yang digunakan adalah kualitatif dengan jenis field research yang dilakukan di Pondok Pesantren Salafiyah Abu Zairi Pakisan Tlogosari Bondowoso. Teknik pengumpulan data memanfaatkan dokumentasi, deep interview, dan observasi partisipasi pasif. Selanjutnya uji keabsahan data menggunakan ketekunan pengamatan, triangulasi sumber dan teknik dengan mengadopsi analisis data model interaktif Miles, Huberman dan Saldana yang terdiri dari pengumpulan data, kondensasi data, penyajian data, penarikan kesimpulan/ Verifikasi. Hasil penelitian ini menunjukkan bahwa pertama, Kiai Muhammad Holid berhasil menerapkan kepemimpinan transformasional melalui unsur-unsur utama dari teori Bass (1999) yang meliputi: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, dan Individualized Consideration kepada seluruh warga pesantren. Kedua, untuk mewujudkan pesantren entrepreneur berbasis sufisme Kiai Muhammad Holid membentuk sistem pendidikan entrepreneur aktif di lembaga formal dan pendidikan tasawuf amaliyah di pesantren. Ketiga, Kepemimpinan transformasional Kiai Muhammad Holid memberikan efektifitas nyata dalam meningkatkan komitmen, keterlibatan, dan loyalitas pendidik dan santri di pondok pesantren. Kata Kunci: Kepemimpinan Transformasional, Pesantren Entrepreneur, Pesantren Sufisme.